Analysis of dominant factors related to the implementation of patient safety culture in the inpatient installation - Zuharni Zuharni; Novirman Novirman; Asrul Asrul; Fauzi Fauzi; Erian Erian; Febrian Febrian; Irna Nursanti (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Patient safety` culture in Indonesia is regulated through ministerial policies emphasizing leadership, teamwork, and staff support. Despite initiatives such as HSOPSC and SAQ, implementation remains partial, with strengths in leadership and teamwork but weaknesses in incident reporting and communication. Leadership, knowledge, attitudes, motivation, and communication significantly influence safety culture outcomes. Purpose: To analyze the dominant factors related to patient safety culture. Method: Correlation research design with cross-sectional and analysis approaches was conducted at Batang Hari Hospital from February – March 2025. A simple random sampling technique was applied, yielding a final sample of 99 respondents. Data collection was conducted using a structured questionnaire. Data analysis was conducted using the chi-square test with a 95% confidence level, where p-values below 0.05 indicated statistical significance. Multivariate analysis was subsequently performed through binary logistic regression with a stepwise approach Results: Leadership, knowledge, attitude, motivation, and communication in relation to patient safety culture yielded p-values less than 0.05. The dominant factors in patient safety implementation culture are leadership (p=0.045), knowledge (p=0.000), and communication (p=0.017). Conclusion: There is a relationship between leadership, knowledge, attitude, motivation, communication and patient safety culture. Knowledge emerges as the most dominant factors in the implementation of patient safety culture.